Nature of Migration in Upper Kosi Watershed of Kumaon Himalaya, Almora District, Uttarakhand - Singh, Ashutosh; Singh, S.B. (National Geographical Journal of India, 2022)
Man is not only the beneficiary of the resource development and utilization but also the most potent and dynamic agent of production. Human resource as an active and important resource has significant role to adjust himself with the environment and then adjusts the environment too. There is a direct relationship between population, environment and economic development. Present paper tries to explain the general demographic condition and nature of migration in Upper Kosi watershed of Kumaon Himalaya, Uttarakhand.